An analysis of the impact of PV farms on airport operation - Adam Mroziński; Patrycja Walichnowska; Adam Idzikowski; Ali Al-Zubiedy; Raid Salman Fahad (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2023)
Large PV installations are being built increasingly often in areas close to airports in Poland and around the world. These are not only roof installations but also large PV farms, allowing not only the supply of the energy for the airport itself but also the ability to sell the excess energy produced. The applied PV installations may cause in some cases negative impact in the form of e.g., electromagnetic fields and light reflections which may limit the visibility of pilots and air traffic controllers. The article presents an overview of various negative impacts of PV farms on the workings of an airport and the main factors influencing the occurrence of certain threats have been diagnosed. An assessment of the usefulness of the tool and method for simulation and the reduction of possible negative impacts is also presented.